Trifolium isthmocarpum Brot: biosaline agriculture for forage and livestock production - Bennani K.; Al Faiz C. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Trifolium isthmocarpum Brot. (Leguminosae), occurs in different habitats in Morocco. It grows in moderately saline areas where traditional forage legumes cannot be cultivated. However, its existence has not been widely studied despite its good palatability. The salt tolerance was studied between natural field conditions and greenhouse. The extensive field studies have recorded the species in many different habitats ranging from healthy agricultural lands to abandoned saline areas. The plants maintained high nodulation capacity (ranging between 70% and 97%) and nitrogenise activities (average 2.05 μmol C2H4 plant-1 h-1) in different habitats. Shoot systems of plants collected from salt-affected soils exhibited higher concentrations of Na+ and Cl- than those collected from healthy soils. Greenhouse experiments showed that germination percentage and vigor value of the studied species was not significantly (P > 0.05) affected at 160 mM NaCl, and that 25% of the germination ability was maintained when growing on substrates containing 220 mM NaCl. The growth rate of seedlings was not significantly affected by 160 mM NaCl but was reduced by 38% under 220 mM NaCl. This study recommends the cultivation of T. isthmocarpum in salt-affected soils, which are widespread and pose a problem for the farmers of Morocco and other countries in the world’s arid belt.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)